Auditor Expertise: Evidence from the Public Sector - Mark Schelker (Center for Research in Economics, Management and the Arts (CREMA), 2011)
Public Auditors are fundamental institutions to supervise government agents. Without accurate information principals would find it hard to make adequate decisions. Since agents face strong incentives to misreport, competent audits of financial information are crucial. This paper is the first attempt to study the relationship between auditor expertise and fiscal performance. More competent auditors are more effective supervisors; they reduce the leeway of agents to misreport and improve fiscal outcomes. The empirical results support this hypothesis. I find that States requiring the auditor to hold a professional degree feature significantly lower debt and expenditures as well as higher credit ratings.
Keywords: H11; D70; H10; 330; public auditor; auditor expertise; auditor competence